An examination of Beethoven's Sonata for piano and violoncello, Op. 5 No. 1, Boccherini's Concerto in B-flat Major for cello, Bach's Suite no. 3 for unaccompanied Violoncello in C Major, and Inman's Suite for Unaccompanied Violoncello in C-sharp Minor - Inman, Michael V. (Kansas State University, 2008)
This document contains an overview of the music performed in my graduate cello recital. Included is biographical information about the composers, historical background, theoretical analysis, stylistic and technical considerations. The recital was given at 5:45 p.m., April 28, 2008, in All Faiths Chapel, Kansas State University with pianist William Wingfield. Program: Sonata in F Major for Piano and Violoncello, Op. 5, No. 1, by Ludwig van Beethoven, Concerto in B-flat Major for Cello and Piano, by Luigi Boccherini, ed. by Friedrich Grützmacher, and Suite No. 3 for Unaccompanied Cello in C major by Johann Sebastian Bach. Also included is an in-depth look at the Suite for Unaccompanied Cello in C-sharp Minor, which was performed by David Littrell at a recital given at 5:45 p.m., May 6, 2008 in All Faiths Chapel, Kansas State University. This recital featured works by Michael V. Inman. Program: Short Pieces for Trumpet, Bass and Percussion, Elegie for Anyone, Matrix I, and Suite for Unaccompanied Cello in C-sharp Minor.
Keywords: Cello; Composition; Inman; Bach; Beethoven; Boccherini; Music (0413)